Celebrative Talk. Enrique's Homemade Algebraic Geometry. - Tocino-Sánchez, Alicia (My University, 2023)
During the talk, Enrique Arrondo's life and mathematical research were highlighted, intertwining his career with a touch of history and significant photos that captured important moments in Enrique's life. Enrique's fascination with mathematics was ignited at an early age, propelling him to become a prodigious thinker. Scholarships and fellowships paved the way for him in his academic pursuits, both locally and internationally. Enrique's contributions to the field of mathematics were remarkable. His interest in algebraic geometry led to numerous publications in prestigious journals, cementing his reputation as an exceptional mind in his field by continuing to advance the resolution of Hartshorne's conjecture. A summary was made of each of the topics he covered, including congruences, vector fibrations without intermediate cohomology, projections on Grassmannian varieties and his advances related with low codimension bundles. In addition, the new lines of research that were created from the results of Enrique's research were presented in the talk.
Keywords: Geometría algebraica; Matemáticos; Arrondo Esteban, Enrique - Homenajes; Algebraic geometry; Congruences; Vector bundles without intermediate cohomology